Sangria terapêutica: estudo comparativo entre os perfis dos procedimentos realizados em março e abril de 2016 a 2018, no Centro de Hemoterapia de Sergipe - Correia, André Gomes (2019)
Objective: the study aims to compare the profile of therapeutic phlebotomies performed at Sergipe's Blood Center (HEMOSE), over the two-month period of March/April of 2016 through 2018. Methods: it was performed an exploratory retrospective descriptive study using secondary data available in medical records.The study's population was composed of 153 patients that received therapeutic phlebotomy at HEMOSE in the two-month period of March/April of 2016 through 2018. All participants were 18 years or older and were borned in the State of Sergipe. The information gathered ranged from the socio-demographic data to the clinical and pathological data used as indication for the phlebotomies. Results: Out of 153 patients, 54 received phlebotomy during March/April in 2016, 42 in 2017 and 57 in 2018. There was a male predominance of 92,59%, 92,86% e 91,23%, respectively. The prevalent age group was 51 to 60 years old in the studied months of 2016 and 2017, while in 2018 it was 41 to 50. The most frequent diagnoses were secondary hyperferritinemia, hereditary Hemochromatosis and Polycythemia Vera in all studied time periods. A small number of intercurrences were observed and, over the years, there was a slight decrease in the frequency of complications during bloodletting. Conclusions: The profile of patients undergoing phlebotomy in the HEMOSE resembles most of the variables to the findings of other studies. Furthermore, in comparing the three studied time periods, there were no significant discrepancies in the patients profiles nor in the procedures parameters.